Life and Works of Rabindra Nath Tagore: Exploring the Multifaceted Works and Impact of Rabindra Nath Tagore (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Rabindranath Tagore (1861-1941) was primarily a poet, yet his work was not limited to poetry. Hehas made significant contributions to the economics of religion and education, politics and socialtransformation, moral regeneration, and economic recovery. Rabindranath Tagore was a brilliantphilosopher, poet, novelist, playwright, and prophet. On May 7, 1961, he was born in Calcutta to a welleducated,rich, and well-respected family. His father, Mahrishi Devandranath Tagore, was mostlyresponsible for his schooling. Rabindranath studied Sanskrit, Indian philosophy, and astronomicalphilosophy. In English, Rabindranath Tagore is a famous Indian poet who is extremely nationalistic. In allof his poetry, plays, and short stories, he expresses his social and patriotic worldview. He was awardeda magnificent prize in 1913 for his amazing poetry, 'Gitanjali.' Man lives in a culture that values thedevelopment of his personality. Rabindranath Tagore was one of India's most well-known poets, and hisworks have a significant impact on Indian literature.